2021
DOI: 10.1371/journal.pone.0252870
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of contralateral hand involvement in the operation of the Delft Self-Grasping Hand, an adjustable passive prosthesis

Abstract: The Delft Self-Grasping Hand is an adjustable passive prosthesis operated using the concept of tenodesis (where opening and closing of the hand is mechanically linked to the flexion and extension of the wrist). As a purely mechanical device that does not require harnessing, the Self-Grasping Hand offers a promising alternative to current prostheses. However, the contralateral hand is almost always required to operate the mechanism to release a grasp and is sometimes also used to help form the grasp; hence limi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(17 citation statements)
references
References 19 publications
1
16
0
Order By: Relevance
“…In this study, comparisons were drawn to existing data from a study of the SGH [ 4 ]. The methodology for data capture was matched as closely as possible to that described in the previous paper.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, comparisons were drawn to existing data from a study of the SGH [ 4 ]. The methodology for data capture was matched as closely as possible to that described in the previous paper.…”
Section: Methodsmentioning
confidence: 99%
“…They were all right-handed, anatomically intact, and had no upper-limb impairments. As the previous trial had limited information on the demographics of its participants, it was decided to source individuals for the mHand trial from the same location as those who took part in the SGH trial, the University of Salford [ 4 ]. Though this does not guarantee the populations to be equivalent, it is believed that this would aid in achieving this goal.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…BP prosthesis users' design priorities and needs have remained virtually unchanged for decades [33,44,49,50], and little attention has been given to broadening the design choices available to them. Recently, the "Self-Grasping Hand" was developed (for adults with hand absence) at the Delft University of Technology [57,58] to address the need for a purely mechanical device that does not require harnessing. However, the Self-Grasping Hand is a passive-adjustable device that does not provide the user with continuous control over grasping movement compared to active UL prostheses.…”
Section: Introductionmentioning
confidence: 99%
“…We asked participants to use the SGH over two weeks in their own Initial laboratory testing of the SGH, with healthy anatomically intact adult volunteers performing activities of daily living using the SGH fitted to a prosthesis simulator, was promising, indicating that it was used more frequently than a conventional passive hand [6,7]. Further lab-based testing, also with anatomically intact adult volunteers performing the Southampton Hand Assessment Procedure (SHAP), quantified the amount of contralateral hand involvement in the operation of the SGH [8]. They found that the percentage of task time where the user was reliant on the contralateral hand remained relatively unchanged (~30%) with practice.…”
Section: Introductionmentioning
confidence: 99%